Related to the Causes of Death in Rheumatoid Arthritis Associations : Study Description - Quispe Mena, Elard (1998)
OBJETIVE:To determine the standardized mortality ratio (Tl \ IE ) and causes of death attributable to the disease or its treatment in patients with rheumatoid arthritis. MATERIAL AND METHODS : An observational , retrospective, longitudinal and descriptive study of pediatric patients with RA was assessed medical records ( criteria of the ARA / CAR ) , who attended the Rheumatology Section, Central Hospital of Air Force was conducted Peru , from July 1976 to April 1993. For the calculation of TME was used as population mortality rate during the study period 9.5 /1 000, according to the Ministry of Health. RESULTS : 245 patients were attended in 17 years, of whom 38 died (15%). They were least satisfied with the prescribed treatment (24 % vs. 14%). The causes of death according to the classification given by Wolfe were attributable to the disease or its treatment 44 % (16 patients) , unrelated 36 % (13 patients) , Contributory 16% (six patients). No information was found in three patients. CONCLUSIONS: TME for the study group is 1.63 . The most frequent causes of death in RA are attributable (lung involvement due to treatment), followed by the Contributory (infectious) and unrelated (primary or metastatic tumors).